Annual Report on the Working of State Electricity Boards and Electricity Departments May, 1989 - Planning Commission (Planning Commission, 1989)
The Report attempts to study the growth and performance of Electricity Supply Undertakings in India in recent years with particular reference to the 1985-86 - 1989-90 period. The undertakings covered are the public utilities in the public sector mainly, i.e. the State Electricity Boards(SEBs),Electricity Departments(EDs) of the States and the Union Territories(UTs) and some Central Government Undertakings. To lend completeness to the coverage, the data pertaining to private sector public utilities has also been indicated wherever the data is available.
(Power & Energy Division) Planning Commission
(Power & Energy Division) Planning Commission